2020
DOI: 10.1177/0033294120918806
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Neuroticism on Internet Addiction in College Students: A Structure Equation Modeling Analysis

Abstract: In the recent decade, increased severity of Internet addiction has been the focus of considerable attention. This research aimed to explore the relationships between neuroticism and Internet addiction. A total of 459 undergraduate students in China participating in this study completed self-report measures of neuroticism, impulsivity, and Internet addiction. The results showed that neuroticism, impulsivity, and Internet addiction were significantly and positively correlated with one other. The structural equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
5
8
0
Order By: Relevance
“…The present study found that depression and neuroticism were significantly lower, and actual social support and self-esteem were significantly higher with non-IA group compared to IA group. These results corresponded with previous studies on IA [ 19 , 20 , 22 , 23 , 26 , 27 , 30 , 31 ]. However, when entered after other psychological and sociological risk factors, these factors could not significantly predict Internet addiction in the logistic regression analyses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study found that depression and neuroticism were significantly lower, and actual social support and self-esteem were significantly higher with non-IA group compared to IA group. These results corresponded with previous studies on IA [ 19 , 20 , 22 , 23 , 26 , 27 , 30 , 31 ]. However, when entered after other psychological and sociological risk factors, these factors could not significantly predict Internet addiction in the logistic regression analyses.…”
Section: Discussionsupporting
confidence: 93%
“…In the psychological dimension, this study discovered that impulsivity was positively related to IA, which was consistent with past researches [ 13 , 20 , 21 , 62 ]. Potential contributions of psychosocial risk factors of IA were further analyzed using a forward logistic regression analyses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The cross-sectional study comprised 619 students (7.1% males, mean age 22 ± 3 years). The engagement rate of 45.8% was comparable with previously reported engagement rates in students' surveys (31). Majority of the students studied health and veterinary sciences (36.7%) and social sciences (30.2%).…”
Section: Resultssupporting
confidence: 83%
“…A study by Yücens and Üzer (30) analyzed factors related to PIU in a sample of 392 medical students in Turkey, suggesting that mental distress factors rather than impulsivity play a cardinal role in PIU (30). However, the study by Zhang (31) comprising 459 undergraduate students in China found that impulsivity in particular mediated the relationship between PIU and neuroticism (31). A recent Italian study involving 244 university students found that PIU was associated with high attentional impulsivity and depressive symptoms (32).…”
Section: Introductionmentioning
confidence: 99%